2021
DOI: 10.33448/rsd-v10i10.18634
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do extrato de tribulus terrestris na histomorfologia cardíaca e fisiologia testicular de ratos

Abstract: O Tribulus terrestris (TT) é uma planta originária da Índia, conhecida como Abrolo ou “Videira-de-punctura”.  São muitas as incertezas relacionadas aos efeitos do TT na potência física de atleta, nos níveis de testosterona e como afrodisíaco. Há poucos relatos do efeito do TT no sistema cardiovascular, contudo citam que pode existir uma correlação negativa entre consumo do TT e atividade da enzima conversora de angiotensina. Neste estudo avaliamos o efeito do TT no ganho de peso, na concentração sérica da test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It was reported that T. terrestris effectively prevented weight gain without causing any changes in the energy balance of the diet, testosterone production, or the histo-morphometry of the heart in rats [ 61 ]. The objective of this research aimed to examine the impact of T. terrestris extracts dissolved in water on endothelial injury in spontaneously hypertensive rats (SHR) and their protective effects on human umbilical vein endothelial cells (HUVECs) against damage induced by Angiotensin II (Ang II).…”
Section: Phytopharmacological Activities/medicinal Propertiesmentioning
confidence: 99%
“…It was reported that T. terrestris effectively prevented weight gain without causing any changes in the energy balance of the diet, testosterone production, or the histo-morphometry of the heart in rats [ 61 ]. The objective of this research aimed to examine the impact of T. terrestris extracts dissolved in water on endothelial injury in spontaneously hypertensive rats (SHR) and their protective effects on human umbilical vein endothelial cells (HUVECs) against damage induced by Angiotensin II (Ang II).…”
Section: Phytopharmacological Activities/medicinal Propertiesmentioning
confidence: 99%